Association between systemic immune-inflammatory index and diabetes mellitus: mediation analysis involving obesity indicators in the NHANES - Chen, Yongze; Huang, Ruixian; Mai, Zhenhua; Chen, Hao; Zhang, Jingjing; Zhao, Le; Yang, Zihua; Yu, Haibing; Kong, Danli; Ding, Yuanlin (Frontiers in Public Health, 2024)
Background: Inflammation and obesity have been widely recognized to play a key role in Diabetes mellitus (DM), and there exists a complex interplay between them. We aimed to clarify the relationship between inflammation and DM, as well as the mediating role of obesity in the relationship.: Based on the National Health and Nutrition Examination Survey (NHANES) 2005-2018.Univariate analyses of continuous and categorical variables were performed using t-test, ANOVA, and χ2 test, respectively. Logistic regression was used to analyze the relationship between Systemic Immune-Inflammatory Index (SII) or natural logarithm (Ln)-SII and DM in three different models.Mediation analysis was used to determine whether four obesity indicators, including body mass index This is a provisional file, not the final typeset article (BMI), waist circumference (WC), visceral adiposity index (VAI) and lipid accumulation product index (LAP), mediated the relationship between SII and DM.Results: A total of 9,301 participants were included, and the levels of SII and obesity indicators (BMI, WC, LAP, and VAI) were higher in individuals with DM (p  0.001). In all three models, SII and Ln-SII demonstrated a positive correlation with the risk of DM and a significant dose-response relationship was found (p-trend  0.05). Furthermore, BMI and WC were associated with SII and the risk of DM in all three models (p  0.001). Mediation analysis showed that BMI and WC mediated the relationship between SII with DM, as well as Ln-SII and DM, with respective mediation proportions of 9.34% and 12.14% for SII and 10.23% and 13.67% for Ln-SII (p  0.001).Our findings suggest that increased SII levels were associated with a higher risk of DM, and BMI and WC played a critical mediating role in the relationship between SII and DM.